Risk factors for and management of cognitive dysfunction in multiple sclerosis - Benedict, Ralph H. B.; Zivadinov, Robert (Nature reviews. Neurology, 2011)
Cognitive impairment is commonly observed in patients with multiple sclerosis (MS), often with a heterogeneous neuropsychological presentation among patients. Benedict and Zivadinov describe the clinical features and neuropsychological tests for cognitive dysfunction in MS with a particular focus on the risk factors for this disorder. Protective factors and potential therapy for cognitive impairment in MS are also discussed. Cognitive impairment is common in multiple sclerosis (MS), especially when assessed by neuropsychological tests that emphasize mental processing speed, episodic memory, and some aspects of executive function. In this Review, we question why some MS patients develop severe impairment in cognitive abilities, while cognitive ability remains intact in others. We find that the heterogeneity in neuropsychological presentation among patients with MS reflects the influence of many factors, including genetics, sex, intelligence, disease course, comorbid neuropsychiatric illness, and health behaviors. Neuropsychological deficits are also robustly correlated with brain MRI metrics. Male patients with early evidence of cerebral gray matter atrophy are most prone to impairment, whereas high premorbid intelligence improves the neuropsychological prognosis. Routine evaluation of cognition is useful for helping patients to navigate problems related to activities of daily living and work disability and, if reliable methods are employed, cognitive decline can be detected and included among the many clinical signs of disease progression or treatment failure. Pharmacological treatments for neuropsychological impairment are on the horizon, although presently no firm medical indications exist for the condition. Key Points Multiple sclerosis (MS) is both an inflammatory and neurodegenerative disease, with cognition affected in roughly 50% of patients Cognitive impairment is most commonly detected on tests of mental processing speed and episodic memory Neuropsychological testing is sensitive to MS cognitive disorder and can be applied in brief, routine evaluations Male patients with low education or intelligence, early onset of MS, and evidence of cerebral gray matter atrophy seem most prone to impairment, whereas high premorbid intelligence is protective To date, evidence for any particular medical therapy improving cognition in MS has been inconsistent, despite being an area of intense investigation Future MS clinical trials should include cognitive outcome measures and use neuropsychological tests that are reliable and are known to reveal clinically meaningful changes